Adaptation responses to increasing drought frequency1. (31st May 2017) - Adamson, David; Loch, Adam; Schwabe, Kurt
Abstract : Using state contingent analysis, we discuss how and why irrigators adapt to alternative water supply signals. Focusing on the timing of water allocations, we explore inherent differences in the demand for water by two key irrigation sectors: annual and perennial producers. The analysis explores the reliability of alternative water property right bundles and how reduced allocations across time influence alternative responses by producers. Our findings are then extended to explore how management strategies could adapt to two possible future drier state types: (i) where an average reduction in water supply is experienced; and (ii) where drought becomes more frequent. The combination of these findings is subsequently used to discuss the role water reform policy plays in dealing with current and future climate scenarios.